2021
DOI: 10.1038/s41598-020-80555-z
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the origin, course and branching pattern of dorsalis pedis artery with clinical significance

Abstract: Pulsations of the dorsalis pedis artery are commonly used to evaluate the peripheral arterial diseases like thromboangiitis obliterans (TAO) or Buerger’s disease, in lower limbs. Dorsalis pedis artery is a direct extension from the anterior tibial artery and major vascular supply for the dorsum of the foot. But arterial variations in lower limbs are common due to rich distal anastomoses around the ankle joint. Absence of dorsalis pedis arterial pulse does not indicate peripheral arterial disease always as it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…In contrast, our prevalence rate was lower than previously reported rates of 52%, 20 53.3%, 28 54.7%, 19 56%, 26 65.6%, 4 67.5%, 14 and 67.5%. 10 Moreover, 3 further studies have reported rates of 90%, 25 96%, 23 and 98% 21 ; however, these high rates for the standard anatomical course of the DPA are questionable because they are so far away from the findings of the majority of other researchers. Overall, their study found the arterial network of the foot to show the normal "textbook" anatomy, which is a very rare finding.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In contrast, our prevalence rate was lower than previously reported rates of 52%, 20 53.3%, 28 54.7%, 19 56%, 26 65.6%, 4 67.5%, 14 and 67.5%. 10 Moreover, 3 further studies have reported rates of 90%, 25 96%, 23 and 98% 21 ; however, these high rates for the standard anatomical course of the DPA are questionable because they are so far away from the findings of the majority of other researchers. Overall, their study found the arterial network of the foot to show the normal "textbook" anatomy, which is a very rare finding.…”
Section: Discussionmentioning
confidence: 93%
“…There are many reports of variations in the standard branching pattern of the DPA. 5,10,15,17,19,20,22 The Lisfranc joint, also known as the tarsometatarsal (TMT) joint, can be fused in patients with osteoarthritis or injury. Marks et al 16 and Alberta et al 1 compared the use of plates and screws for fusion of the TMT joints during loading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In the sense of number, this artery itself can be found in double or even the increase in distal branching as atypical trifurcation. 23 Furthermore, the branching patterns on the dorsum of foot were surprisingly various as classified up to 9 types with the typical pattern at only 36.4% in prevalence. 22 All of these knowledge play an important role in reducing the risk of complications from intervention dealing with this artery or the structures nearby, eg., nerves, bones and joints.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the orientation variation of the distal part of DPA described in Table 2, there have been additional variations in terms of number, location and also its branching pattern. [21][22][23] For example, distance variation due to DPA location in relation to the tarsal navicular bone was established to provide the practical data for the midfoot surgery. 21 In the sense of number, this artery itself can be found in double or even the increase in distal branching as atypical trifurcation.…”
Section: Discussionmentioning
confidence: 99%